Variação espacial do efeito de borda em povoamento de teca desbastado - Silveira, Aline Ferreira (2020)
The volume of wood in a forest is a quantitative variable that, when properly determined, allows the management and planning of the use of forest resources. Starting from the hypothesis that the trees located on the borderhave different dendrometric characteristics when compared to those in theinterior of the stand, presenting greater height, diameter, and volume and that this superiority gradually decreases until the size of the trees becomes homogeneous with the internal trees. The objective of this work was to knowthe spatial distribution of the edge effect and its contribution to the production and productivity of teak stands. The study was carried out in an equestrian and homogeneous teak settlement, of seminal origin, with 17 years of age, locatedin the municipality of Nossa Senhora do Livramento, Mato Grosso. In the data collection, the quality of the site was considered, and the inventory of thepermanent plots was carried out, in addition to a census of the diameter at 1.3mfrom the trees (D1.3) and the respective georeferencing of the trees. Thestudied treatment variables were height (h), diameter 1.3 m from the ground (D1.3 m), basal area (G) and volume (V). The data were evaluated both qualitatively through the dominance classification and quantitatively, comparing the dendrometric variables using the Wilcoxon test. From the analysis of the data, it was possible to determine that in teak stands of seminal origin, at seventeen years old, submitted to three thinning, the edge effect increases the frequency of individuals in the upper classes of dominance in the trees located on the edge in relation to the internal trees of the plots. And that the edge effect influences the average yield of the plots and varies from the edge to the interior,reflecting the increase in the basal area and the volume of plots, regardless of the site class.